An in vivo study of Hypericum perforatum in a niosomal topical drug delivery system - Mohamed Ali; Amira Abdel Motaal; Mohammed A. Ahmed; Abdulrhman Alsayari; Omaima N. El-Gazayerly (Taylor & Francis Group, 2018)
The active compounds present in Hypericum perforatum L. (Hypericaceae) include hyperforin, hypericins and flavonoids, which are assumed to be responsible for the activity of the extract in the treatment of wounds and scars. The present study aimed to incorporate H. perforatum extract standardized to a known content of phloroglucinols, naphthodianthrones and polyphenolic compounds into an effective transdermal drug delivery system capable of entrapping both lipophilic and hydrophilic constituents in the form of niosomal gels for wound treatment. An 80% ethanol extract (HE) was prepared on a pilot scale using DIG-MAZ. An HPLC-DAD holistic profile was established for HE and was standardized to contain 3.4 ± 4 rutin, 1.1 ± 3 chlorogenic acid, 0.5 ± 2 quercitrin, 2.8 ± 2 hyperforin, and 0.51 ± 3% w/w total hypericins. Niosomes were prepared using the modified reverse phase evaporation technique (REV). The wound healing effect of the gel was tested on 16 adult mongrel dogs. A significant decrease in the inflammatory cell count (18.4 ± 5.3) was recorded in the niosomal gel 1.5% NaCMC-treated group at the 7th day post wounding. It induced a marked regression in the inflammatory phase and enhanced the early beginning of the proliferative phase of wound healing. After 21 days, it showed complete re-epithelization, formation of new matrix fibers and significant reduction in the wound size, compared to the control and the Panthenol® 2% cream treated groups. This is the first study of H. perforatum in a niosomal topical drug delivery system.